2005
DOI: 10.1007/s11284-005-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term grazing on soil organic carbon content in semiarid steppes in Inner Mongolia

Abstract: To clarify the response of soil organic carbon (SOC) content to season-long grazing in the semiarid typical steppes of Inner Mongolia, we examined the aboveground biomass and SOC in both grazing (G-site) and no grazing (NG-site) sites in two typical steppes dominated by Leymus chinensis and Stipa grandis, as well as one seriously degraded L. chinensis grassland dominated by Artemisia frigida. The NG-sites had been fenced for 20 years in L. chinensis and S. grandis grasslands and for 10 years in A. frigida gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 44 publications
11
71
3
5
Order By: Relevance
“…In Bloemfontein, relatively high soil pH occurs under high grazing, compared with low grazing ( Table 2). In the Inner Mongolia region of China, a similar result was found by Cui et al (2005), who reported that soil pH decreased with a longterm (30 grazing, compared with continuous grazing. As to alkaline grasslands, Jeddi and Chaieb (2010) reported that a long-term (12 years) exclusion of livestock grazing increased species richness and decreased soil pH from moderate alkalinity to slight alkalinity in degraded arid steppe of Tunisia.…”
Section: Grazing and Soil Chemical Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…In Bloemfontein, relatively high soil pH occurs under high grazing, compared with low grazing ( Table 2). In the Inner Mongolia region of China, a similar result was found by Cui et al (2005), who reported that soil pH decreased with a longterm (30 grazing, compared with continuous grazing. As to alkaline grasslands, Jeddi and Chaieb (2010) reported that a long-term (12 years) exclusion of livestock grazing increased species richness and decreased soil pH from moderate alkalinity to slight alkalinity in degraded arid steppe of Tunisia.…”
Section: Grazing and Soil Chemical Propertiessupporting
confidence: 78%
“…Animal trampling may have a major impact on soil structure and subsequently alter the soil water infiltration and availability to plants (Yates, 2000). Grazing is further associated with changes in soil pH and organic carbon, and soil nutrients such as N, P and K (Cui et al, 2005;Jeddi and Chaieb, 2010;Tefera et al, 2010;Yates, 2010). Accordingly, species composition and biomass production may be influenced through the direct effects of defoliation and trampling, and the indirect effects of nutrient enrichment and depletion (Snyman, 1998; Fernandez-Gimenez and Allen-Diaz, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As water was the major factor that limited plant growth in natural grasslands (St Clair et al, 2009), the increases in aboveground production were significantly greater in areas with the preferred amount of precipitation (>300 mm). Piñeiro et al (2009) concluded that the effects of grazing exclusion on root biomass were positive at mesic locations (400-850 mm of MAP) (Fuhlendorf et al, 2002;Kauffman et al, 2004;Xie and Wittig, 2004;Derner et al, 2006;Gao et al, 2011), but negative at humid and dry conditions (McNaughton et al, 1998;Frank et al, 2002;Pucheta et al, 2004;Reeder et al, 2004;Cui et al, 2005). Similarly, in our study, MAP ranged from 134 mm to 752 mm across all experimental sites.…”
Section: Factors Influencing the Effects Of Grazing Exclusion On Carbsupporting
confidence: 70%
“…However, the reduction in TC and TN concentrations with the grazing intensity in our study could also be ascribed to the following reasons. First, the soil organic matter (SOM) is determined by main inputs from decomposition of aboveground and belowground vegetation litter and animal excreta and main outputs though the mineralization and leaching of carbon and nitrogen (Golluscio et al 2009;Cui et al 2005). Second, grazing markedly reduced vegetation coverage (Fig.…”
Section: X) and The Vegetation Characteristics (Y)mentioning
confidence: 99%